Enhancing Constructability through Construction-Phase Design Adaptations: The Case Study of the Jenelata Dam Project - Yusuf, Muh; Abdurrahman, M. Asad; Latief, Rusdi Usman (Engineering, Technology & Applied Science Research, 2026)
This study explores how construction-phase design changes affect constructability performance in large-scale dam projects, using the Jenelata Dam Project in Indonesia as a case study. Three questions are tackled: (1) how design process factors relate to constructability, (2) how much these factors impact constructability performance, and (3) how design adaptations during construction influence time, cost, and constructability. A mixed-method approach was used, combining a survey of 32 project stakeholders (owners, consultants, and contractors), field observations, and document analysis. Quantitative analysis included Pearson correlation and multiple linear regression, with an R² of 0.786, showing strong explanatory power of design process variables. The results indicate that all design process factors are positively and significantly related to constructability, with Iterative and Adaptive Design being the most influential (β = 0.408). Qualitative validation shows that early and systematic design adaptations, such as replacing frame beams and hydroseeding with Geomat Type III for slope protection, and changing foundation treatment from vertical to rim grouting, led to significant improvements, including a 70% reduction in construction time and cost savings up to 61.3%. These findings provide empirical evidence that well-managed construction-phase design changes can improve constructability when coordinated and driven by data. The study offers practical insights for better integration of design and construction, and for managing design changes adaptively in complex dam projects.